Two new frog species (Microhylidae: Cophixalus) from boulder habitats on Cape York Peninsula, north-east Australia - Hoskin, Conrad J.; Aland, Kieran (Zootaxa, 2011)
Australia has a highly localised but diverse radiation of microhylid frogs. 18 species are described from north-east Queensland (14 Cophixalus and 4 Austrochaperina), most with highly localised montane distributions. While most species are small (10-25 mm) rainforest species, two differ dramatically in ecology and morphology. Cophixalus saxatilis and C. zweifeli inhabit isolated areas of jumbled boulder-pile habitat and are considerably larger than all other species (30-45 mm). Here we describe two new species of large, boulder dwelling Cophixalus from the Pascoe River region of Cape York Peninsula. Cophixalus kulakula sp. nov. occurs in piled boulder habitat amongst rainforest in the Tozer Range area, while Cophixalus pakayakulangun sp. nov. occurs in similar habitat in the Kennedy Hills region north of the Pascoe River. These are the most northerly sites for Cophixalus in Australia and both occur in rainforest areas not occupied by other species of Cophixalus. Both species are large (snout-vent length > 40 mm) and of similar morphology to the other two boulder-dwelling species. Cophixalus kulakula sp. nov. and C. pakayakulangun sp. nov. differ from each other and from all other described Cophixalus genetically and in aspects of colour pattern and morphology. The call of C. kulakula sp. nov. is also unique, but the call of C. pakayakulangun sp. nov. remains unknown. The two new species are each others closest relatives (albeit with approximately 8% genetic divergence for 12S and 16S mtDNA) and are allied to C. ornatus. The diet of both species consists primarily of ants. Both species have highly localised distributions but are abundant within these and are probably secure.